Characteristics of Stillbirths Associated With Diabetes in a Diverse U.S. Cohort. Issue 6 (December 2020) - Page, Jessica M.; Allshouse, Amanda A.; Cassimatis, Irina; Smid, Marcela C.; Arslan, Erol; Thorsten, Vanessa; Parker, Corette; Varner, Michael W.; Dudley, Donald J.; Saade, George R.; Goldenberg, Robert L.; Stoll, Barbara J.; et al.
Abstract : OBJECTIVE: To characterize stillbirths associated with pregestational diabetes and gestational diabetes mellitus (GDM) in a large, prospective, U.S. case–control study. METHODS: A secondary analysis of stillbirths among patients enrolled in a prospective; multisite; geographically, racially, and ethnically diverse case–control study in the United States was performed. Singleton gestations with complete information regarding diabetes status and with a complete postmortem evaluation were included. A standard evaluation protocol for stillbirth cases included postmortem evaluation, placental pathology, clinical testing as performed at the discretion of the health care professional, and a recommended panel of tests. A potential cause of death was assigned to stillbirth cases using a standardized classification tool. Demographic and delivery characteristics among women with pregestational diabetes and GDM were compared with characteristics of women with no diabetes in pairwise comparisons using χ 2 or two-sample t tests as appropriate. Sensitivity analysis was performed excluding pregnancies with genetic conditions or major fetal malformations. RESULTS: Of 455 stillbirth cases included in the primary analysis, women with stillbirth and diabetes were more likely to be older than 35 years and have a higher body mass index. They were also more likely to have a gestational hypertensive disorder than women without diabetes (28% vs 9.1%; P <.001). Women with pregestational diabetes had more large-for-gestational-age (LGA) neonates (26% vs 3.4%; P <.001). Stillbirths occurred more often at term in women with pregestational diabetes (36%) and those with GDM (52%). Maternal medical complications, including pregestational diabetes and others, were more often identified as a probable or possible cause of death among stillbirths with maternal diabetes (43% vs 4%, P <.001) as compared with stillbirths without diabetes. CONCLUSION: Compared with stillbirths in women with no diabetes, stillbirths among women with pregestational diabetes and GDM occur later in pregnancy and are associated with hypertensive disorders of pregnancy, maternal medical complications, and LGA. Abstract : Stillbirths in pregnancies affected by diabetes differ from other stillbirth cases in that they occur later in gestation and have greater association with gestational hypertensive disorders and large-for-gestational-age fetuses.